Evaluating the Impact of Smart Infusion Pump Interoperability on Reducing Medication Administration Errors: A Systematic Literature Review - Borrelli EP; Lucaci JD; Wilson NS; Taneja A; Weiss M; Beer I (Medical Devices: Evidence and Research)
Eric P Borrelli,1 Julia D Lucaci,2 Nicole S Wilson,3 Ashley Taneja,2 Mia Weiss,2 Idal Beer3 1Health Economics and Outcomes Research, MMS, Becton, Dickinson and Company, San Diego, CA, USA; 2HEOR Strategic Planning; Becton, Dickinson and Company, Franklin Lakes, NJ, USA; 3Medical Affairs, MMS, Becton, Dickinson and Company, San Diego, CA, USACorrespondence: Eric P Borrelli, Health Economics and Outcomes Research (HEOR), Becton, Dickinson and Company, 3750 Torrey View Ct, San Diego, CA, 92130, USA, Email EricBorrelli@gmail.comPurpose: Medication administration errors remain a persistent issue in the US healthcare system, impacting patient safety and leading to worsened outcomes, including increased mortality. Smart infusion pump interoperability with electronic health records (EHRs) has the potential to reduce intravenous (IV) medication administration errors. Smart Infusion pumps safely deliver IV medications using drug libraries that set standard dosing limits. Interoperability is their ability to wirelessly connect to EHRs to receive medications orders directly minimizing error-prone manual programming steps. However, despite being implemented over a decade ago, its real-world impact remains largely underexplored.Methods and Materials: A systematic literature review (SLR) of PubMed/Medline and Embase in November 2024 identified peer-reviewed studies assessing medication administration errors pre- and post- interoperability implementation in the inpatient hospital setting. The primary outcome measured error types directly impacted by interoperability. The secondary outcome assessed the cumulative reduction in medication administration errors.Results: Three studies met the inclusion criteria, spanning general community hospitals, pediatric facilities, and intensive care units (ICUs). For the primary outcome of assessing medication administration errors impactable by interoperability, interoperability implementation resulted in a 15.4% to 54.8% reduction in specific medication administration errors. For the secondary outcome of all medication administration errors, the cumulative reductions in medication administration errors post-implementation ranged from 21.2% to 90.5%, with variability influenced by baseline compliance, study setting, and patient populations.Conclusion: Smart infusion pump interoperability demonstrated consistent potential to enhance medication safety by addressing key error types and reducing cumulative errors in real-world settings. However, future research is needed to assess its impact on adverse drug events, clinician workflows, and patient outcomes. These findings underscore the importance of tailored implementation strategies to maximize interoperability’s effectiveness in improving patient safety.Plain Language Summary: Medication administration errors are a common issue in hospitals in the United States, with the potential to impact patient safety and lead to worsened outcomes. Smart infusion pump interoperability with electronic health records has the potential to reduce intravenous (IV) medication administration errors. Smart infusion pumps are infusion pumps that have drug libraries with standardized dosing. Interoperability is the technological advancement that wirelessly connects smart infusion pumps with EHRs, allowing medication orders to transfer directly instead of being entered manually. However, despite being implemented over a decade ago, its real-world impact remains largely underexplored in clinical practice. Therefore, we conducted a systematic literature review to identify studies assessing the impact of implementing smart infusion pump interoperability on medication administration errors in the inpatient hospital setting. Our review identified three studies assessing this impact. Two of the studies assessed our primary outcome of assessing medication administration errors impactable by interoperability and saw a post-implementation reduction ranging from 15.4% to 54.8%. All three of the studies assessed our secondary outcome of all medication administration errors and saw post-implementation reductions range from 21.2% to 90.5% post-implementation. Smart infusion pump interoperability demonstrated consistent potential to enhance medication safety by addressing key error types and reducing cumulative errors in real-world settings.Keywords: smart infusion pump, interoperability, auto programming, medication administration errors, infusion errors, preventable adverse events